POLA DAKWAH MULTIKULTURAL DI KOTA PALU - Syamsuri Syamsuri (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2014)
This paper deals with a variety of da’wah in Palu. It is assumed that polarization of people leads to cultural consequences, which are manifested in the form of Islamic organization, such as Alkhairaat, Darul Dakwah wal Irsyad (DDI), and so forth. As a result, suspicion emerges among native people towards rituals carried out by newcomers. This paper is based on multicultural, which emphasizes on universal justice which is inherent in the inividuals regardless of their association to the group. The result shows that there is ‚mutual understanding‛ between Muslim preachers from various Islamic organizations. The patterns of da’wah activities in Palu emerged due to the dynamics of economic struggle (mareso masagena), the flexibility of the local culture (nosampesuvu), and the wisdom of community leaders, both formal and informal (tataguna).